Junie B. Jones is a graduation girl - Park, Barbara; Brunkus, Denise (New York : Scholastic, 2002)
Junie B. Jones has just turned six and is looking forward to her kindergarten graduation, but when grape juice stains the white gown she couldn't resist trying on, she is afraid graduation is ruined.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Keywords: Kindergarten -- Juvenile fiction; Commencement ceremonies -- Juvenile fiction; Kindergarten -- Fiction; Graduation (School) -- Fiction